Tingkat Cemaran Logam Berat Pada Air Sungai Batanghari Provinsi Jambi berdasarkan Indeks C/P (Contamination/Pollution) - Shally Yanova; Kory Asi Mariana Siagian; Rizki Gusanti (Jurnal Daur Lingkungan, 2020)
This research has been conducted in July to August 2020. The purpose of this study is to find out the heavy metal content of Hg, Cd, Pb, Mn, and Fe in the Batanghari River water of Jambi Province and determine the level of contamination by referring to PP No.82 Year 2001. The research site was conducted in Aur Duri 1 and Aur Duri 2 Jambi Provinces. Research on heavy metal content in water was conducted at 6 measurement points consisting of 3 measurement points in the Aur Duri region 1 upper and lower of the river and 3 measurement points in the Aur Duri region 2 the upper and lower of the river. Determination of river water sampling point is done using purposive sampling method. Based on the results of this study, it can be concluded that the Batanghari River water of Jambi Province has been very heavily polluted with Hg and Fe metals, if referring to PP No.82 Year 2001 Class I. The content of Mn metal in Batanghari River water mostly belongs to the category of fairly polluted metal Mn.While the metal content of Cd and Pb belongs to the category is not contaminated.